COMMUNITY PARTICIPATION IN THE IRRIGATION NETWORK DEVELOPMENT AND MANAGEMENT PROGRAM IN THE NGULANAN VILLAGE AREA OF DANDER DISTRICT - Monly, Lusiana; Ari, Ismu Rini Dwi; Usman, Fadly (Directorate of Research and Community Service (DRPM), 2024)
This research uses logic model analysis to evaluate the effectiveness of the HIPPA Program (Productive and Safe Rural Irrigation Revitalization Program) in Ngulanan Village. The main objectives of the research are to assess the program's compliance with the technical guidelines of P3TGAI in 2021 and to understand the impact of community participation on program effectiveness. The analytical method involves the formation of a logical framework that encompasses program stages and issues related to sanitation infrastructure, as well as evaluating program compliance based on established criteria. The research results indicate that approximately 53% of the program's success criteria have been met, but there is still room for improvement, especially regarding community participation and effective communication. The analysis also reveals disparities among stakeholders, which can affect community participation. Implementation factors such as a lack of effective communication and resource constraints are also obstacles to program implementation. Therefore, efforts are needed to enhance community participation, improve communication, and allocate resources more efficiently to enhance the effectiveness of the HIPPA Program in the future. The research concludes that evaluation adopting the technical guidelines of P3TGAI 2021 is an essential instrument in assessing and improving program quality, along with a commitment to providing a positive and sustainable impact for the Ngulanan Village community.